1982
DOI: 10.1159/000233170
|View full text |Cite
|
Sign up to set email alerts
|

Induction of an Allergic Air-Pouch Inflammation in Rats

Abstract: An allergic air pouch inflammation was induced on the dorsum of rats using azobenzenearsonate-conjugated acetyl bovine serum albumin as an antigen. Rats were immunized by intradermal injection with 5 mg of the antigen in 0.5 ml Freund’s complete adjuvant saline (1:1) emulsion. 9 days after the immunization 8 ml of air was injected subcutaneously on the dorsum, and 24 h later 4 ml of 2% sodium carboxymethyl cellulose solution containing 2 mg of the antigen was injected into the preformed air pouch to provoke th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
4

Year Published

1982
1982
1997
1997

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 14 publications
1
47
1
4
Order By: Relevance
“…We have previously shown that humoral immunological responses including anaphylaxis and Arthus type hy persensitivity reactions may be involved in the early phase of this inflammation [40][41][42]. Therefore, dietary enrichment of (n-3)-fatty acids might influence the immunological responses before inflammatory re sponses occurred in the air pouch.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that humoral immunological responses including anaphylaxis and Arthus type hy persensitivity reactions may be involved in the early phase of this inflammation [40][41][42]. Therefore, dietary enrichment of (n-3)-fatty acids might influence the immunological responses before inflammatory re sponses occurred in the air pouch.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization and induction of allergic air pouch inflamma tion were carried out as described previously [23,24]. Male rats of the Sprague-Dawley strain, specific pathogen-free, weighing 140-150g (Charles River Japan, Inc., Kanagawa, Japan), were used.…”
Section: Induction Of Anaphylactic Reactionmentioning
confidence: 99%
“…In an experimental model of allergic inflammation of air pouch type in rats, which has been devised in our laboratory [23,24], anaphylactic increase of vas cular permeability is induced [25,26] by injecting the antigen solution into the preformed air pouch on the dorsum. The present paper was undertaken to ex amine whether PAF is synthesized in the locus of the inflammatory site in this anaphylactic phase of the allergic inflammation, in order to get further insight into the physiological role of PAF in the anaphylactic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of experiments to identify the difference between allergic and non-allergic inflammation employing an air pouch-type inflammation model in rats 1985;Tsurufuji et al, 1982;Hirasawa et al, 1986;Watanabe et al,1987;1990), focused especially on the qualitative difference in the function of infiltrated leucocytes, we found (Watanabe et al, 1994) that the leucocytes ' Author for correspondence. infiltrated into the pouch fluid in the allergic inflammation model are much more active than those in the non-allergic inflammation model with respect to neutrophil chemotactic factor production.…”
Section: Introductionmentioning
confidence: 99%